2015
DOI: 10.1002/msc.1091
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis, Management and Assessment of Adults with Joint Hypermobility Syndrome: A UK-Wide Survey of Physiotherapy Practice

Abstract: Joint hypermobility syndrome (JHS) is a heritable disorder associated with excessive joint range of motion and pain in the absence of inflammatory joint disease. It is a relatively common cause of musculoskeletal pain but is generally understood to be under‐recognized and poorly managed in clinical practice. The present study therefore aimed to identify how JHS is diagnosed, managed and assessed in routine physiotherapy practice. A survey tool was developed from similar physiotherapy surveys of musculoskeletal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 26 publications
1
24
0
1
Order By: Relevance
“…A subsequent UK-wide survey conducted by the research team has revealed that this pattern of care fits very well with what is delivered by physiotherapists nationally. 39 By agreeing such broad guiding principles, the research team wanted to ensure that the physiotherapy intervention package developed stood the best chance of being adopted in practice, should it ultimately prove to be beneficial.…”
Section: The Research Projectmentioning
confidence: 99%
See 3 more Smart Citations
“…A subsequent UK-wide survey conducted by the research team has revealed that this pattern of care fits very well with what is delivered by physiotherapists nationally. 39 By agreeing such broad guiding principles, the research team wanted to ensure that the physiotherapy intervention package developed stood the best chance of being adopted in practice, should it ultimately prove to be beneficial.…”
Section: The Research Projectmentioning
confidence: 99%
“…These were related primarily to the resource context within which most physiotherapy services operate 39 but also mirrored best practice as conducted at North Bristol NHS Trust. First, it was agreed that the intervention would be delivered on a one-to-one basis, as the needs of individual patients were considered to be so varied.…”
Section: Development Of the Physiotherapy Interventionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of the current study and the descriptions reported in the literature may indicate that the treatment of hypermobile persons should not be too localized or guided by a biomechanical approach only. There are some current studies, which took this into consideration such as Palmer et al [37]. They concluded in their study that the physiotherapeutic management of persons experiencing a hypermobility syndrome should be focused on advice, education, exercise and self-management, but more specific research is still required [21,37].…”
Section: Discussionmentioning
confidence: 99%